Cooperative Mechanism for Energy Transportation and Storage in Internet of Energy - Weigang Hou; Guoda Tian; Lei Guo; Xiaojie Wang; Xu Zhang; Zhaolong Ning (IEEE Access)
To improve the energy conversion ability and well utilize renewable resources, J. Rifkin first put forward the concept of “Internet of energy IoE)”. Although a peer-to-peer energy sharing mechanism is achieved through bi-directional energy transportation, the approach to solving cooperative energy transportation and storage still needs improving. Traditionally, the redundant energy will be wasted if it cannot be consumed by power load. In fact, the redundant energy can be stored to supply power loads in the future. For this end, we investigate cooperative energy transportation and storage for IoEs in terms of problem analysis, algorithm design, and platform development. After demonstrating the feasibility condition and proving the NP-hard of our problem, we derive the optimal solution by the reduction from a classic knapsack problem. We also design novel heuristics followed by different energy storage strategies. In addition, based on software-defined networking (SDN), a complementary platform is developed to make an effective decision for cooperative energy transportation and storage using heuristics above. Both simulation and experimental results demonstrate the effectiveness of our solutions.